Water contents of clinopyroxenes from sub-arc mantle peridotites - Turner, Michael; Turner, Simon; Blatter, Dawnika; Maury, Rene; Perfit, Michael; Yogodzinski, Gene (Island Arc, 2017)
One poorly constrained reservoir of the Earth's water budget is that of clinopyroxene in metasomatised, mantle peridotites. This study presents reconnaissance Sensitive High-Resolution, Ion Microprobe-Stable Isotope (SHRIMP-SI) determinations of the H 2 O contents of (dominantly) clinopyroxenes in rare mantle xenoliths from four different subduction zones, i.e. Mexico, Kamchatka, Philippines, and New Britain (Tabar-Feni island chain) as well as one intra-plate setting (western Victoria). All of the sub-arc xenoliths have been metasomatised and carry strong arc trace element signatures. Average measured H 2 O contents of the pyroxenes range from 70 ppm to 510ppm whereas calculated bulk H 2 O contents range from 88 ppm to 3737ppm if the variable presence of amphibole is taken into account. In contrast, the intra-plate, continental mantle xenolith from western Victoria has higher water contents (3447ppm) but was metasomatised by alkali and/or carbonatitic melts and does not carry a subduction-related signature. Material similar to the sub-arc peridotites can either be accreted to the base of the lithosphere or potentially be transported by convection deeper into the mantle where it will lose water due to amphibole breakdown.